PERSEPSI PRODUK COFFEE SHOP CUPPAJO DAN REPURCHASE INTENTION DI YOGYAKARTA - koko setyawan (JURNAL EKOBIS DEWANTARA, 2018)
The purpose of this research is: The variable in this study was Perceived Servicescape, Perceived Quality, Perceived price, Perceived Value and satisfaction. The population in this research is the consumer or society has ever made a purchase coffee shop Cuppajo Yogyakarta. Sampling technique used was accidental sampling method the selection of samples taken from members of a population selected by chance match a particular purpose. Engineering data collection using the questionnaire. Analysis of multiple regression analysis was used. Keywords: Perceived Servicescape, Perceived Quality, Perceived Price, Perceived value, Satisfaction.